2020
DOI: 10.1038/s41598-020-69382-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neck/shoulder pain among public hospital workers in China and its associated factors: a cross-sectional study

Abstract: Studies have reported that neck and/or shoulder pain (nSp) was prevalent and a non-ignorable occupational health problem in healthcare providers. Considering data deficiency on NSP, we aimed to investigate the prevalence and sick leave absence of NSP among public hospital workers in Shandong, china and to explore the associated factors for chronic nSp. A self-administered questionnaire including the Dutch Musculoskeletal Questionnaire and Modified Nordic Musculoskeletal Questionnaire was filled in by 30,520 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
1
9
1
1
Order By: Relevance
“…Nurses working for more than seven hours per day for continuous six days (>42 h) were less likely (lower odds) to have lower back and shoulder pain as compared to those who worked for six days at seven hours per day (42 h) in the current study, which is consistent with the result of Koohpayehzadeh et al [37] for shoulder pain in 512 nursing personnel in the Iran Medical University of Medical Sciences in Tehran and the findings of [38] regarding low back pain. In contrast with our study results, other studies found that there was no significant association between working hours and MSD pain [3,39,40].…”
Section: Discussioncontrasting
confidence: 99%
“…Nurses working for more than seven hours per day for continuous six days (>42 h) were less likely (lower odds) to have lower back and shoulder pain as compared to those who worked for six days at seven hours per day (42 h) in the current study, which is consistent with the result of Koohpayehzadeh et al [37] for shoulder pain in 512 nursing personnel in the Iran Medical University of Medical Sciences in Tehran and the findings of [38] regarding low back pain. In contrast with our study results, other studies found that there was no significant association between working hours and MSD pain [3,39,40].…”
Section: Discussioncontrasting
confidence: 99%
“…Neck pain is a major health problem worldwide with an annual prevalence rates of 37.2% (range 16.7-75.1%) [ 1 ]. Healthcare professionals have developed various management and prevention measures for neck pain; paradoxically, neck pain is highly prevalent among healthcare professionals due to the nature of their work [ 2 , 3 ]. However, it has been suggested that healthcare professionals experience neck pain even before they start working.…”
Section: Introductionmentioning
confidence: 99%
“…Darüber erhöht eine einseitige Belastung des Schultergürtels z. B. bei Schwimmern oder Personen, deren berufliche Tätigkeit ein Verharren in gebeugter und gedrehter Haltung erfordert, die Auftretenswahrscheinlichkeit für Schulterschmerzen 5 6 7 8 .…”
Section: Zusammenfassungunclassified